2002
DOI: 10.5713/ajas.2002.1364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Controlled Compensatory Growth on Mammary Gland Development and Lactation in Rats

Abstract: The objective of this study was to examine the effect of compensatory growth nutritional regimen on mammary gland growth and lactation. One hundred twenty-two Sprague Dawley female rats (35 days of age) were randomly assigned to either a control or a stair-step compensatory nutrition (SSCN) feeding regimen or an alternating 2-2-3-3-week schedule beginning with 40% energy restriction for 2 weeks followed by re-alimentation (control diet) for 2 weeks. Pup weight gain and milk yield were improved 8% and 8 to 15%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They found that both prepartum and postpartum mammogenesis were reduced in relation to the number of placentas removed. A strong impact of pregnancy is also implied by studies demonstrating that nutritional events during hormone-sensitive growth phases, especially during late gestation, can significantly affect mammary development and subsequent lactation performance (Kim et al, 1998;Moon and Park, 1999;Moon and Park, 2002) in dairy cattle, beef heifers and female rats. These improvements in performance have been linked to increased cell proliferation with concurrent elevations in gene expression of key genes involved in cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that both prepartum and postpartum mammogenesis were reduced in relation to the number of placentas removed. A strong impact of pregnancy is also implied by studies demonstrating that nutritional events during hormone-sensitive growth phases, especially during late gestation, can significantly affect mammary development and subsequent lactation performance (Kim et al, 1998;Moon and Park, 1999;Moon and Park, 2002) in dairy cattle, beef heifers and female rats. These improvements in performance have been linked to increased cell proliferation with concurrent elevations in gene expression of key genes involved in cell proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the β‐casein gene is higher (40–74%) in mammary tissues during late gestation from heifers reared on a compensatory nutrition regimen than in those from conventionally raised heifers. In early lactating mammary tissues from rats on compensatory nutrition, there is also a pronounced increase in β‐casein message, amounting to 132% and 48% for first and second lactation cycles, respectively (3). The α‐ and γ‐casein and whey acidic protein mRNA are also higher in lactating mammary tissues from rats reared on a compensatory nutrition regimen (21).…”
Section: Nutritionally Directed Compensatory Mammary Development and mentioning
confidence: 99%
“…Finally, insulin-like growth factor-I (IGF-I), which regulates mammary gland development through both promotion of cell cycle progression and inhibition of apoptosis (29), is lower in mammary tissues from the compensatory group than in those from the control group during early lactation and higher during late lactation (3). The expression of IGF-I during early lactation may be a possible negative factor for milk production in rats, and the compensatory-mediated increase in IGF-I mRNA during late lactation may have a suppressing effect on apoptosis of mammary cells.…”
Section: Lactation Potentialmentioning
confidence: 99%
“…The use of compensatory feeding regimens to stimulate mammary development and lactation potential is an avenue that has received quite a bit of interest in rodents and heifers. In rats, a stair-step nutrition model inducing compensatory growth during peripuberty only or during peripuberty and gestation (Moon and Park, 2002) improves lactation performance by modulation of mammary cell differentiation. These changes were accompanied by increases in casein β (CSN2; Moon and Park, 2002) and ornithine decarbolyxase (ODC1; Kim et al, 1998) mRNA abundance in mammary tissues.…”
Section: Introductionmentioning
confidence: 99%
“…In rats, a stair-step nutrition model inducing compensatory growth during peripuberty only or during peripuberty and gestation (Moon and Park, 2002) improves lactation performance by modulation of mammary cell differentiation. These changes were accompanied by increases in casein β (CSN2; Moon and Park, 2002) and ornithine decarbolyxase (ODC1; Kim et al, 1998) mRNA abundance in mammary tissues. In heifers, nutritionally directed compensatory growth increased milk yield along with CSN2 gene expression in mammary tissue in late gestation and lactation Ford and Park, 2001).…”
Section: Introductionmentioning
confidence: 99%